Greater and More Natural Use of the Upper Limbs During Everyday Life by Former Amputees Versus Prosthesis Users. (March 2022) - Frey, Scott; Motawar, Binal; Buchanan, Kelli; Kaufman, Christina; Stevens, Phil; Cirstea, Carmen; Morrow, Sean
Hand loss profoundly impacts daily functioning. Reversal of amputation through hand replantation or transplantation offers an alternative to prosthetics for some. Whether recipients exhibit more extensive and natural limb use during everyday life than prosthesis users is, however, unknown. We asked unilateral, below-elbow amputees (N = 22), hand graft recipients (transplants N = 4; replants N = 2), and healthy matched controls (N = 20) to wear wireless accelerometers distally on their forearms/prostheses and proximally on their upper arms. These units captured limb activity over 3 days within participants' natural environments. Graft recipients exhibited heavier reliance on their affected hands compared to amputees' reliance on their prostheses, P < .001. Likewise, reliance on the injured side upper arm was also greater for hand graft recipients than amputees, regardless of whether they were wearing their prostheses, P < .05 in both cases. Hand graft recipients, like healthy controls, also relied more on forearm vs upper arm movements when controlling their limbs, P < .001. Compared with conventional prosthesis users, graft recipients exhibited more extensive and natural functioning of the upper limbs during everyday activities. This information is an important addition to other considerations when evaluating risk-benefit of these treatment alternatives.